Certain New Classes of Analytic Functions with Varying Arguments. (30th January 2013) - El-Ashwah, R. M.; Aouf, M. K.; Hassan, A. A. M.; Hassan, A. H.
Abstract : We introduce certain new classes κ − V S T ( α, β ) and κ − V U C V ( α, β ), which represent the κ uniformly starlike functions of order α and type β with varying arguments and the κ uniformly convex functions of order α and type β with varying arguments, respectively. Moreover, we give coefficients estimates, distortion theorems, and extreme points of these classes.